KAJIAN PENYUSUTAN BERAT BADAN DAN PENINGKATAN SUHU TUBUH AYAM BROILER TERIMPLEMENTASI KURKUMA (CURCUMA LONGA), GULA AREN (ARENGA PINATA) AKIBAT LAMA TRANSPORTASI - Fredy J. Nangoy (Universitas Padjadjaran, 2012)
Transport processes of broiler chicken pen to the slaughterhouse research can lead to stress. Transportation stress substantially unavoidable, but that does not mean that the negative effects of stress can not be reduced. Efforts to suppress the detrimental effects of stress alternative because of transportation one can do with management prior, through provision of rations containing turmeric (Curcuma longa) and drinking water containing palm sugar (Arenga pinata). The objective of this study is obtained implementation and delivery of palm sugar turmeric pre-tarnsportation to maintain the stability performance of broiler chickens. The study was conducted on 15 - 12 - 2011 in West Java Regency Sumedang District Village Buahdua Bentar Cibitung at farmer group chairman Mr Haji Mulyadi. Transportation routes from the village carried Bentar Cibitung - Cipadung - Nagrag or 2 hours, Village Bentar Cibitung - Cipadung - Nagrag - Cipadung - Tanjungkarta - Cipadung - Nagrag or 3 hours, Village Bentar Cibitung - Cipadung - Nagrag - Cipadung - Nagrag - Congeang - Nagrag or 4 hours. Each car transport speed 50-60 km/hour. Research carried out by using the method of factorial experimental design Completely Randomized Experiment 3 x 3 x 3. A factor is the transportation of animal with three replications, namely A1 is a 2 hour transportation, A2 is a 3 hour, and A3 is a4 hour transportation ; anti stress factor B with three replications, namely B1 is turmeric, palm sugar 2%, B2 is turmeric, palm sugar 3%, B3 turmeric, and palm sugar 4%. Statistical tests performed to test the influence of variance and differences between treatments were examined using by different test real honest.The study found that the implementation of turmeric, palm sugar in different rations and drinking water despite a weight loss ranging from 33.33 up to 70.33 g, increased body temperature ranges from 0.70 up to 1.30°C.